Existence of The Minister of Agrarian and Spatial/ Regulatory National Land Agency to Department of Water Resources Management and Spatial Planning (DPSDAPR) in The Brebes District - M. Zaenal Arifin; Jawade hafidz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To know the existence of the Minister of Agrarian And Spatial / National Land Agency Regulatory Department of Water Resources Management and Spatial Planning (DPSDAPR) in Brebes. 2) To know the reality of the implementation of the Regulation Department of Water Resources Management and Spatial Planning (DPSDAPR) in Brebes. 3) To identify weaknesses and solutions from reality Regulations Department of Water Resources Management and Spatial Planning (DPSDAPR) in Brebes. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by qualitative descriptive method.Based on the results of data analysis concluded that: 1) the existence of the Minister of Agrarian And Spatial / National Land Agency are dualism Brebes Regional policy against Spatial affairs field. 2) Reality Spatial implementation is still predominantly carried out by the Region in Brebes the Department of Water Resources Management and Spatial Planning.Keywords: Judicial Review; Existence; Spatial.